(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
This study examines the risk and return of common stock investments on the Bombay Stock Exchange, with a focus on common stocks from four industries: banking, pharmaceuticals, automobiles, and information technology. All companies' equities were listed on the Bombay Stock Exchange. Investors have different perspectives on risk and rewards. They invest in opportunities that carry a certain level of risk. Secondary data on share prices on the Bombay Stock Exchange (BSE) was collected over a twelve-month period (January 21 to December 21). Several tools have been employed, including average (returns), standard deviation (risk), variance, and coefficient of variation (CV). It was discovered that the entire IT industry has ranked first out of four selected indexes for its greatest performance and the lowest variability in the return. It also depicted the lowest fluctuations in the prices. The last rank was of Banking industry for highest fluctuations in the prices. So, Banking industry is very much risky with fluctuated rate of return.